Biogenic Synthesis of Photosensitive Magnesium Oxide Nanoparticles Using Citron Waste Peel Extract and Evaluation of Their Antibacterial and Anticarcinogenic Potential - Nawal M. Al Musayeib; Musarat Amina; Farah Maqsood; Kholoud A. Bokhary; Nada S. Alrashidi (Bioinorganic Chemistry and Applications)
Background. Magnesium oxide nanoparticles (MgONPs) have been fabricated by several approaches, including green chemistry approach due to diverse application and versatile features. Objectives. The current study aimed to prepare a convenient, biocompatible, and economically viable MgONPs using waste citron peel extract (CP-MgONPs) to evaluate their biological applications. Methods. The CP-MgONPs were synthesized by a sustainable approach from extract of waste citron peel both as capping and reducing agents without use of any hazardous material. The physicochemical features of formed CP-MgONPs were determined by sophisticated analytical and microscopic techniques. The biogenic CP-MgONPs were examined for their antibacterial, anticarcinogenic, and photocatalytic attributes. Results. A prominent absorption peak in the UV-Vis spectra at 284 nm was the distinguishing characteristic of the CP-MgONPs. The scanning electron microscopy (SEM) reveals polyhedral morphology of nanoparticles with slight agglomeration of CP-MgONPs. The CP-MgONPs exerted excellent antibacterial potencies against six bacterial strains. The CP-MgONPs displayed significant susceptibility towards E. coli (20.72 ± 0.33 mm) and S. aureus (19.52 ± 0.05 mm) with the highest inhibition zones. The anticancer effect of CP-MgONPs was evaluated against HepG2 (IC50 : 15.3 μg·mL−1) cancer cells and exhibited potential anticancer activity. A prompt inversion of cellular injury manifested as impairment of the integrity of the cell membrane, apoptosis, and oxidative stress was observed in treated cells with CP-MgONPs. The biosynthesized CP-MgONPs also conducted successful photocatalytic potential as much as MgO powder under the UV-light using acid orange 8 (AO-8) dye. The degradation performance of CP-MgONPs showed over 94% photocatalytic degradation efficiency of acid orange 8 (AO-8) dyes within a short time.​ Conclusions. Outcomes of this research signify that biogenic CP-MgONPs may be advantageous at low concentrations, with positive environmental impacts.